STUDI TINGKAT KEBISINGAN LALU LINTAS PADA JALAN TIPE 2/2 UD (Studi Kasus : Jalan Pangeran Suryanata Samarinda) - ARIFIN, MOH SYAMSUL (KURVA S JURNAL MAHASISWA, 2018)
Pollution has not only occurred in the air, soil, or water, but also include noise pollution in the form of noise. The noise can be defined as unwanted sound or loud noises. Noise can give effect harmful to health that can lead to deafness, nervous disorders, mental disorders, heart problems, high blood pressure, dizziness and even insomnia. Research on the measurement of the noise level is done around the Mosque Fathul Khair Samarinda, Elementary School 004 Samarinda, and the Islamic Prayer Room Raudhatul Jannah Samarinda. The purpose of this research is to determine the noise level of the environment and compare it with the raw quality of the conducted noise levels around the Mosque Fathul Khair Samarinda, Elementary School 004 Samarinda, and the Islamic Prayer Room Raudhatul Jannah Samarinda with a simple method, i.e. the noise level measurements use the tool in the form of a Sound Level Meter (SLM) carried out for 10 minutes and time reading every 5 seconds. The measurement results show that the level of noise every 5 seconds obtained at each research site that is at the Mosqua Fathul Jannah of 69,51 dBA, elementary School of 70,38 dBA and at the Islamic Prayer Room Raudhatul Jannah of 70,38 dBA. These values exceed the quality standard based on the decision of the Minister of State for the environment no. 48 in 1996 about the Raw noise levels, and according to the regulation of the Minister of health no. 718, 1987 about the noise, the location of this measurement is supposed to enter a zone B, among other School, and Worship Place, with noise around 45 – 55 dB. So in this condition required treatment can lower noise levels, one of them by making the green line or tree planting